The effect of copper on the antifungal activity of polyethyleneimines against quiescent conidia and germlings of Aspergillus nidulans - Dimitris Tsiourvas; Zili Sideratou; Eleni Mavrogonatou; Dimitris Kletsas; Vicky Sophianopoulou; Spiros Gerostathis (Scientific Reports)
Abstract The increase in the number of immunocompromised individuals combined with the severity of fungal infections in the general population has contributed to a significant increase in opportunistic fungal infections, which are often associated with high mortality rates. Although effective, existing antifungal drugs operate via a narrow range of mechanisms, leading to the rapid development of resistance and they primarily target growing host cells. Therefore, the need to develop next-generation antifungal agents that function via a broad range of mechanisms and/or target dormant/quiescent cells is highly important. In the present study, we investigated the characteristics and potential antifungal properties of a series of copper-chelated hyperbranched polyethyleneimines (PEI-Cu) with various molar ratios of Cu2+:primary amino groups of PEI (Cu: N), using the opportunistic pathogen Aspergillus nidulans as a model microorganism. Our results showed that PEI-Cu¼ and PEI–Cu¹⁄₁₆ complexes with Cu: N molar ratios of 1:4 and 1:16, respectively, retain the fungicidal activity of PEI. Cu2+ chelation seemed to delay the internalization of PEI-Cu, but they were found to exhibit apparent fungicidal activity on A. nidulans quiescent conidiospores while they affected hyphal growth rate, redox status and mitochondrial network morphology in A. nidulans germlings. In addition, no cytotoxic effects were observed on normal human skin fibroblasts at concentrations or incubation times that were entirely inhibitory for A. nidulans. Overall, our results suggest that the investigated PEI-Cu complexes are promising antifungals, and their underlying mechanism of action deserves further investigation, especially for use against drug-resistant quiescent fungal cells.